Realistic deployment of hybrid wireless sensor networks based on ZigBee and LoRa for search and rescue applications - Bravo-Arrabal, Juan; Zambrana-López, Pablo; Fernández-Lozano, Juan Jesús; Gómez-Ruiz, José Antonio; Serón-Barba, Javier; García-Cerezo, Alfonso José (IEEE Access, 2022)
Search and Rescue operations in emergency response to natural or human catastrophes have the main objective of locating and rescuing potential victims as fast as possible, thus quick response and accurate actions are mandatory. While standard communications may be affected, a Wireless Sensor Network can be deployed to support the rescue team. This kind of network allows data acquisition close to events and enables persistence over time, among other advantages. However, enhancements must be made to improve the adaptation to this kind of scenario. This work presents two Hybrid Wireless Sensor Networks, based on ZigBee and LoRa, developed to address some of the challenges that Search and Rescue operations pose to the use of Wireless Sensor Networks, and tested in realistic scenarios in cooperation with first responders. Likewise, several software developments that increase the performance of the networks are described. Finally, the conclusions presented, and the lessons learnt are supported by a high amount of data, gathered in realistic exercises in cooperation with civilian and military first responders.
Keywords: Gestión de emergencias - Innovaciones tecnológicas; Graphical user interfaces; ZigBee; LoRa; Internet of Things; Mobile robots; Search and rescue; Emergency services